Normalization of Precarious Work: The European and Brazilian Experience - Previtali, Fabiane Santana; Fagiani, Cílson César (Pontifícia Universidade Católica de São Paulo, 2021)
The objective of this article is to discuss the current expansion and normalization of precarious work in Western Europe and Brazil in the context of Industry 4.0 and the deepening of neoliberal policies under the principles of New Public Management, which in the Brazilian case gained new impetus with the approval of the Labor Reform of the Temer government (2016-2018). The research was based on secondary sources, documents and data analysis for selected periods. The results demonstrate deepening precariousness in the countries and time periods considered, despite increasing rates of employability.